ARISTOLE'S EUDAIMONIA AS REFLECTED IN THE SHORT STORY OF STORY OF THE TWO YOUNG FRIENDS - Manurung, Ontje (Conscientia - Journal on Language, Literature, and Culture, 2023)
Virtues are the key to gain ultimate goal (eudaimonia) which practiced in friendship. These virtues and eudaimonia can be learned from literary works and one among others is through an American Indian short story entitled Story of the Two Young Friends. This study is aim to examine the type of friendship between the characters, Chaske and Hake and to elaborate the eudaimonia - ultimate goal of life - of Chaske. The data gathered from the short story itself are analyzed using objective theory by M.H. Abrams and technique of analyzing the intrinsic element proposed by William Kenney. To support the analysis the writer applies moral philosophical approach which is used to examine the type of friendship between Chaske and Hake and Chaske’s eudaimonia reflected in the short story. The result shows that the friendship between Chaske and Hake is friendship based on virtues and the ultimate goal of Chaske is choosing and making Hake to be his true friend, giving up the woman he loves to Hake, and making Hake’s dream comes true, that is marrying Pretty Feathers.